The Influence of Online Customer Reviews, Ratings, and Discounts on Fashion Purchase Decisions on Shopee E-Commerce - Muhammad Yoga Fernando; Saida Zainurossalamia ZA (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the influence of online customer reviews, online customer ratings, and price discounts on consumers' purchasing decisions for fashion products on the Shopee e-commerce platform. This study employed a quantitative approach using a survey method by distributing questionnaires to 70 respondents who had previously purchased fashion products on Shopee. Data were analyzed using the Partial Least Squares structural equation modeling (PLS-SEM) technique with the assistance of SmartPLS 4 software. The results revealed that online customer reviews had no significant effect on purchase decisions. In contrast, online customer ratings and price discounts had positive and significant effects on consumers' purchasing decisions. These findings suggest that consumers tend to place greater emphasis on star ratings and price incentives than on customer reviews when making purchasing decisions. This study has practical implications for sellers and managers of the Shopee e-commerce platform in enhancing the effectiveness of promotional strategies and product evaluation systems to encourage consumer purchasing decisions.